2021
DOI: 10.31557/apjcp.2021.22.5.1333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Underlying Comorbidities on Mortality in SARS-COV-2 Infected Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: Background: The evidence has shown that SARS CoV-2 infected patients with comorbidities are more likely to have severe disease sequel and mortality. In SARS-CoV-2 infected cancer patients risks associated with other underlying comorbidities might vary from those in non-cancer SARS CoV-2 infected patients. The relative impact of different underlying health conditions among patients with cancer and SARS CoV-2 infection remains yet to be explored. This systematic review aims to explore the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“…Several systematic reviews and meta-analysis have been published since 2020 and they identified several independent risk factors for COVID-19 death: increasing age [2][3][4][5][6][7][8][9][10][11] , male sex 5,[7][8][9][10][11][12][13][14][15] , hypertension 10,11,13,14,[16][17][18] , diabetes mellitus 8,10,11,[13][14][15][16][17][18][19] , obesity 2,6,11 , cardiovascular disease (CVD) 10,11,14,[16][17][18]20 , cerebrovascular disease 11,14,20 , chronic kidney disease (CKD)…”
Section: Introductionmentioning
confidence: 99%
“…Several systematic reviews and meta-analysis have been published since 2020 and they identified several independent risk factors for COVID-19 death: increasing age [2][3][4][5][6][7][8][9][10][11] , male sex 5,[7][8][9][10][11][12][13][14][15] , hypertension 10,11,13,14,[16][17][18] , diabetes mellitus 8,10,11,[13][14][15][16][17][18][19] , obesity 2,6,11 , cardiovascular disease (CVD) 10,11,14,[16][17][18]20 , cerebrovascular disease 11,14,20 , chronic kidney disease (CKD)…”
Section: Introductionmentioning
confidence: 99%
“…The underlying immunosuppressive microenvironment due to dysfunctional immune cell production is a fundamental attribute of the malignancies that drives their pathogenesis (11). Comorbid conditions such as; Hypertension, Cardiovascular diseases, Chronic obstructive pulmonary diseases, Diabetes, Chronic kidney diseases, Cerebrovascular diseases are likely to decrease immunity, impair macrophage and lymphocyte function, and are associated with the pathogenesis of SARS-CoV-2 (12).…”
Section: Introductionmentioning
confidence: 99%
“…Comorbid conditions such as; Hypertension, Cardiovascular diseases, Chronic obstructive pulmonary diseases, Diabetes, Chronic kidney diseases, Cerebrovascular diseases are likely to decrease immunity, impair macrophage and lymphocyte function, and are associated with the pathogenesis of SARS-CoV-2 (12).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations